A Coenzyme‐Independent Decarboxylase/Oxygenase Cascade for the Efficient Synthesis of Vanillin. Issue 15 (27th August 2014) - Furuya, Toshiki; Miura, Misa; Kino, Kuniki
Abstract Vanillin is one of the most widely used flavor compounds in the world as well as a promising versatile building block. The biotechnological production of vanillin from plant‐derived ferulic acid has attracted much attention as a new alternative to chemical synthesis. One limitation of the known metabolic pathway to vanillin is its requirement for expensive coenzymes. Here, we developed a novel route to vanillin from ferulic acid that does not require any coenzymes. This artificial pathway consists of a coenzyme‐independent decarboxylase and a coenzyme‐independent oxygenase. When Escherichia coli cells harboring the decarboxylase/oxygenase cascade were incubated with ferulic acid, the cells efficiently synthesized vanillin (8.0 mM, 1.2 g L−1) via 4‐vinylguaiacol in one pot, without the generation of any detectable aromatic by‐products. The efficient method described here might be applicable to the synthesis of other high‐value chemicals from plant‐derived aromatics.